Bank Selection Process and Market Segmentation: Evidence from Indian Exporting SMEs. (June 2015) - Kaur, Manpreet
Liberalization, privatization and globalization caused by economic reforms have induced severe competition in Indian banking sector. To survive in this contemporary, highly competitive business environment, banks should be able to attract new customers by identifying what is valuable to them and how they make bank selection decision. Small and medium-sized enterprise (SME) exporters have been found to be a very important segment of banks' market because of profit and revenue opportunities presented by them. For appropriate positioning in exporting SMEs' market, banks are not only required to be aware of their bank selection criteria rather they should also be aware of their different segments. In the present study, an effort has been made to identify the bank selection criteria of exporting SMEs as well as to segment them on the basis of the same. Findings revealed timeliness in services and accommodation of credit needs as critical factors considered by exporting SMEs while selecting a bank. Further, two types of SMEs customers have been identified, namely, transaction-oriented and relationship-oriented SMEs. Transaction-oriented SMEs who are newly established and more price-sensitive should be targeted with transaction-oriented strategy which aims at offering better-quality services at lower costs than competing banks. Conversely, relationship-oriented SMEs who are established focus more on bank features as well as on need accommodation; a relationship-oriented strategy can be followed to acquire such customers.